Тимур и его команда: повесть / Аркадий Гайдар - Гайдар Аркадий Петрович (Чтение - лучшее учение, 2016)
Экземпляры: ф.4 (20241025) / Инвентарный номер: 1223 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 14 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44